Analisis Literasi Baca Siswa Melalui Kegiatan Berbahasa Di Kelas II SD Negeri Kaliwlingi 01 - Indah Rizqiyah; Diah Sunarsih; Dedi Romli Triputra (Peneliti.net, 2022)
Analysis of students' reading literacy through of language activities in the second grade of SD Negeri Kaliwlingi 01. The objectives in this study were to: (1) describe the implementation of students' reading literacy in language activities in the class II, (2) describe several supporting factors and inhibiting factors in the reading literacy students of the through language activities in the class II. This study uses a qualitative research approach with a qualitative descriptive research design. Data collection techniques using interviews, non-participant observation, and documentation. The validity of the data is done by triangulation. The triangulation used in this research is source triangulation and technique triangulation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, it was concluded that students' reading literacy through language activities in its implementation was not optimal. Where in the implementation of reading literacy there are some students who are still not fluent in reading and there are also students who can read but are still stammering. Reading literacy is carried out every time the learning is finished when students go home from school, students are called one by one to read a few sentences. This activity aims to find out how students can read and read fluently, the techniques used to be able to read and read fluently and to find out the characters that exist in students. Therefore, with the existence of students' reading literacy through language activities in second grade, it is expected that students have knowledge and skills in reading literacy through language of activities.